2003
DOI: 10.1093/carcin/24.3.385
|View full text |Cite
|
Sign up to set email alerts
|

The role of cyclooxygenase in n-6 and n-3 polyunsaturated fatty acid mediated effects on cell proliferation, PGE2 synthesis and cytotoxicity in human colorectal carcinoma cell lines

Abstract: This study was conducted to investigate the role of the enzyme cyclooxygenase (COX) and its prostaglandin product PGE(2) in n-6 and n-3 polyunsaturated fatty acid (PUFA)-mediated effects on cellular proliferation of two human colorectal carcinoma cell lines. The long chain PUFAs eicosapentaenoic acid (EPA; 20:5n-3) and arachidonic acid (AA; 20:4n-6) both inhibited cell proliferation of Caco-2 cells compared with the long chain fatty acids alpha-linolenic acid (ALA; 18:3n-3) and linoleic acid (LA; 18:2n-6). Nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
7

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 46 publications
3
78
0
7
Order By: Relevance
“…However, previous studies have failed to address the differential effects of n-3 PUFA and n-6 PUFA, and of their combination, on cancer cell growth. In light of several studies that have demonstrated cancer cell growth inhibition by n-3 PUFA or n-6 PUFA [22,23,26] , our data help to clarify the issue of differential effects of n-6 and n-3 PUFAs on apoptosis and cell growth.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, previous studies have failed to address the differential effects of n-3 PUFA and n-6 PUFA, and of their combination, on cancer cell growth. In light of several studies that have demonstrated cancer cell growth inhibition by n-3 PUFA or n-6 PUFA [22,23,26] , our data help to clarify the issue of differential effects of n-6 and n-3 PUFAs on apoptosis and cell growth.…”
Section: Discussionmentioning
confidence: 70%
“…Other results have shown that PGE2 formation and vascular endothelial growth factor expression are suppressed, while apoptosis is induced by DHA and EPA in the HT-29 colon cancer cell line [21] . In contrast, several other studies in colon cancer cell lines have demonstrated that AA as well as DHA or EPA suppresses growth [22,23] . Other studies have found a pro-apoptotic effect of DHA and AA in HT-29 colon cancer cells [24,25] and in the A549 lung cancer cell line [26] .…”
Section: Introductionmentioning
confidence: 81%
“…A number of fatty acids occurring in the human diet, including a-linolenic acid, linoleic acid, docosahexaenoic acid and eicosapentaenoic acid as well as ursolic acid have previously been shown to inhibit COX-2 catalysed prostaglandin biosynthesis and markedly inhibited COX-2 in mice and in in vitro experiments. 33,[44][45][46] In line with this, olive oil and fish oil, which are complex mixtures of fatty acids have been reported to inhibit COX-2 protein expression. 47) Short chain fatty acids are known to modulate different molecular mechanisms of importance in colon cancer cells 48,49) and have been extensively studied for their ability to affect colonic function.…”
Section: )mentioning
confidence: 65%
“…Moreover, R( þ )-methanandamide, a stable analogue of the endocannabinoid anandamide, was recently shown to induce apoptosis of neuroglioma cells via a COX-2-dependent mechanism (Hinz et al, 2004;Eichele et al, 2006). Further evidence supporting the involvement of COX-2-derived PGs in proapoptotic and cytotoxic effects of diverse other substances was provided by studies performed on human leukemia (Chen et al, 2005), C6 rat glioma (Maccarrone et al, 2002), colorectal carcinoma (Dommels et al, 2003) and H-ras-transformed breast epithelial cells (Na et al, 2005).…”
Section: Introductionmentioning
confidence: 99%